Saccharomyces cerevisiae immobilized onto cross-linked chitosan beads: application of a novel material for the removal of dye toxicity - Dilarri, Guilherme [UNESP]; Corso, Carlos Renato [UNESP] (Taylor & Francis Ltd, 2018)
Waste from textile industries can severely harm the environment. Dyes are the main residues of these effluents. Saccharomyces cerevisiae is already known to be an efficient adsorbent for the removal of dyes. However, the lack of applicability and limitation of the use of cell biomass in an industrial treatment makes it impossible to apply them. Thus the aim of this work was to immobilize S. cerevisiae in cross-linked chitosan beads by two different techniques (contact immobilization and encapsulation in the polymer matrix), proposing two new materials for adsorption. Adsorption experiments were carried out to analyse the kinetics, isotherm and thermodynamics adsorptive of the synthesized materials. The adsorption data obtained were compared with the S. cerevisiae biomass and with the cell-free cross-linked chitosan beads to evaluate the efficiency of the two synthesized materials. The Fourier transform infrared spectrophotometer was used to characterize and analyse the main adsorption sites of the tested materials. Bioassays using the microcrustacean Daphnia similis verified if the materials could reduce the toxicity of the medium after its application in the treatment. Both materials synthesized in this work can potentially remove dyes from effluents, in addition to being able to significantly decrease dye toxicity from an aqueous medium.
Keywords: Adsorption; bioassays; biopolymer; bioremediation; textile industries; yeast